CURRENT STATUS OF PARKLAND TREES IN URBANIZED STEPPE AREAS OF THE DNIPRO REGION IN UKRAINE (Ecological Bulletin of Kryvyi Rih District, 2025)
In the anthropogenically altered landscapes of the Dnieper Steppe, the regulation of abiotic atmospheric and soil-forming processes, in particular through the density of artificially created forest ecosystems through dynamic restoration of soil fertility, is, in our opinion, a promising program for the post-war period of restoration of Ukrainian forest resources in the regions. Plant resources are exploited to economic and biological extent. Exploitation in horticulture has led to the fact that a small number of species have been destroyed in the wild and survived in cultivation. Over the past 3-5 years, there has been no clear consensus for most of the Dnipro region on the rates of reduction of introduced tree species and populations of woody plants of natural and artificial origin. The centers of introduced tree species have covered the territory of the Dnipro region of Ukraine with a network of parks and have significantly changed the general appearance of the forest ecosystems of the Dnipro steppe. Parks occupy small areas, but carry significant recreational value. Download. By conducting studies of the species composition of park plantings, the level of vital activity and current state in the conditions of urbanized territories of the Dnipro steppe, counting the number of woody plants, installing the age structure and percentage composition of the tree stand on the example of the park of the city of Dnipro and the city of Kryvyi Rih. Using the method of conducting research on the species composition of park plantings, the level of vital activity and current state in the conditions of urbanized territories of the Dnieper steppe region were determined, the number of woody plants was counted, and the age structure and percentage composition of the tree stand were established using the example of the parks of the city of Dnipro and the city of Kryvyi Rih. Of particular interest now are trees - long-lived, dominant species of the existing dendroflora. They are of great interest as representatives of a valuable gene pool. Based on the work done for each park, an inventory plan and a passport of the municipal facility were drawn up.
Keywords: adaptation strategies of woody plants, features of trees in urban areas, stress, stability of tree stands